Use of High Performance Computing in Agent-Based Social Simulation: A Case Study on Trust-Based Coalition Formation - Rosset, Luciano M.; Nardin, Luis G.; Sichman, Jaime S. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Computer models based on agents have shown to be very useful in the field of social simulation, especially for its versatility and ease to model complex systems. In the context of agent simulations, Nardin and Sichman developed a model for the study of coalition formation among agents, based on trust. Later, the need of more efficient ways for simulating the model was acknowledged in order to explore large-scale scenarios. The solution found was the adoption of a high performance agentbased computing platform. This article intends to explore the use of such platform on the Nardin and Sichman’s model by migrating its code to the Repast HPC tool, which is executed on the Blue Gene/P supercomputer.